CD248+ Cancer-Associated Fibroblasts: A Novel Prognostic and Therapeutic Target for Renal Cell Carcinoma - Xu, Chao; Zhang, Keying; Yang, Fa; Zhou, Xiang; Liu, Shaojie; Li, Yu; Ma, Shanjin; Zhao, Xiaolong; Lu, Tong; Lu, Shiqi; Zhang, JiaYu; Li, Hongji; et al. (Frontiers in Oncology, 2021)
Background The tumor microenvironment (TME) plays an important role in the progression of renal cell carcinoma (RCC). Cancer-associated fibroblasts (CAFs) are considered to constitute a major component of the TME and participate in various tumor-promoting molecular events. We have previously confirmed that CD248 represents a promising biomarker of CAFs, which may provide insight into CAF-based tumor-promoting effects. However, CAF-mediated tumor progression and the potential mechanism of CD248 remain largely unknown in RCC patients. Methods Expression profiling and clinical data of RCC patients were obtained from The Cancer Genome Atlas (TCGA) database. An MCP-counter algorithm and Kaplan–Meier survival analysis were performed to explore the prognostic value of CAFs and CD248, respectively. A Pearson correlation coefficient test and Student’s t-test were employed to evaluate the relationship between immunosuppressive TME and CD248 or CAFs. Immunohistochemistry and immunofluorescence staining were performed to confirm CD248 expression within CAFs. CD248-specific siRNA was used to investigate the potential function of CD248 in CAF tumor promotion. Differentially expressed genes (DEGs), weighted gene co-expression network analysis (WGCNA), and enrichment analysis were conducted to clarify the function of CD248+ CAFs in RCC progression and the associated regulatory mechanism. Results CD248 overexpression and CAF infiltration could predict poor RCC prognosis, which may involve the immunosuppressive TME. CD248 may serve as a promising CAFs biomarker and be involved with the tumor-promoting effect of CAFs. Moreover, CD248+ CAF infiltration may contribute to RCC progression and an immunosuppressive TME through cell-extracellular matrix (ECM) interactions and metabolism regulation. Conclusion CD248+ CAFs participate in the regulation of RCC progression and immunosuppressive TME, which may represent a novel prognostic and therapeutic target for RCC.